2018
DOI: 10.1055/s-0038-1672129
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Based Computed Tomography Angiography in Anterolateral Thigh Perforator Mapping of Chinese Patients

Abstract: Background During reconstructive surgery, anterolateral thigh (ALT) flap harvest is challenging due to variation and uncertainty in perforator distribution. We performed a pilot study to identify the predictive value of catheter-based computed tomography angiography (C-CTA) and traditional CTA (T-CTA) in ALT perforator mapping for patients whose ALT perforators were difficult to identify. Methods Thirty-four consecutive T-CTA/C-CTA-mapped ALT flaps were evaluated for extremity reconstruction. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…Despite its invasive nature, catheter-based CTA may have increased utility in this patient population where muscle disuse atrophy can distort perforators on traditional CTA. 35 Preoperative CTAs for perforator mapping and flap design have been shown to improve outcomes and decrease operative times in breast reconstruction; however, they have yet to be widely used in other forms of perforator flap planning. 35 In a direct comparison between the use of traditional handheld Doppler and CTA in 32 head and neck reconstructions using the ALT flap, Liu et al found significantly decreased major surgical complications, operative time, and length of hospital stay in the CTA group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its invasive nature, catheter-based CTA may have increased utility in this patient population where muscle disuse atrophy can distort perforators on traditional CTA. 35 Preoperative CTAs for perforator mapping and flap design have been shown to improve outcomes and decrease operative times in breast reconstruction; however, they have yet to be widely used in other forms of perforator flap planning. 35 In a direct comparison between the use of traditional handheld Doppler and CTA in 32 head and neck reconstructions using the ALT flap, Liu et al found significantly decreased major surgical complications, operative time, and length of hospital stay in the CTA group.…”
Section: Discussionmentioning
confidence: 99%
“…35 Preoperative CTAs for perforator mapping and flap design have been shown to improve outcomes and decrease operative times in breast reconstruction; however, they have yet to be widely used in other forms of perforator flap planning. 35 In a direct comparison between the use of traditional handheld Doppler and CTA in 32 head and neck reconstructions using the ALT flap, Liu et al found significantly decreased major surgical complications, operative time, and length of hospital stay in the CTA group. 16 Despite these documented benefits, further studies are required to determine the cost effectiveness of obtaining routine CTA for preoperative mapping in ALT reconstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforator variability and availability can make it difficult to harvest a compound ALTP flap. Preoperative CTA can demonstrate the patient's vascular anatomy and aid perforator selection and operative success , but CTA still needs to be improved (Wang et al, 2019). In our practice, we combine CTA with a handheld Doppler to confirm the location of the perforators prior to surgery, which significantly reduces the The primary limitations of this report were the lack of a comparative group and lack of a standardized measure for long-term outcomes after complex extremity soft tissue reconstruction.…”
Section: Casementioning
confidence: 99%
“…With interest, we read the article, "Catheter-Based Computed Tomography Angiography in Anterolateral Thigh Perforator Mapping of Chinese Patients," by Wang et al, published in Journal of Reconstructive Microsurgery in October 2018. 1 Free anterolateral thigh (ALT) flap is a common reconstructive surgical modality. However, due to the unpredictability of the perforator vessels, ALT flap has been bothersome even for the experienced microsurgeons.…”
mentioning
confidence: 99%